Maternal nutritional status and low birth weight in Khone-Kaen Province, Thailand - Sayasane, Thongsavath
This hospital based case-control study was conducted from September to December 1999. The purpose of the study was to identify the association between the delivery of low birth weight baby and five indicators of maternal nutritional status, namely: maternal weight at the first trimester of pregnancy, maternal height, maternal BMI at the first trimester, maternal BMI at 28-30 weeks of pregnancy, and maternal weight gain during pregnancy. The study subjects were composed of 82 cases of low birth weight babies and 328 control babies who were delivered full term, singleton, without congenital abnormality, and whose mothers did not have maternal complications.In the crude analysis, the following indicators were statistically associated with the delivery of low birth weight babies; maternal weight at the first trimester of pregnancy (OR=2.20; 95CI:1.15-4.18), maternal height (OR=3.07; 95CI:1.64-5.74), maternal BMI at the first trimester of pregnancy (OR=2.0; 95CI:1.0-3.94), and maternal weight gain (OR=2.51; 95CI:1.24-5.05). There was not enough evidence to say that there is a significant relationship between maternal BMI at 28-30 weeks of pregnancy and the delivery of low birth weight baby (OR=1.16; 95CI:0.63-2.15).The result of the final moderl in the logistic regression analysis showed that after controlling for maternal occupation and past history of low birth weight, maternal BMI at the first trimester of pregnancy and maternal height were significant risk factors of LBW. Furthermore, parity interacted with maternal weight gain such that among nulliparous mothers, low maternal weight gain was associated with a high risk of low birth weight (OR=5.2; 95CI:1.83-14.74). Among multiparous women, maternal weight gain was not associated with low birth weight.Public health intervention like nutritional education and caloric supplementation should be provided, especially to pregnant women at the first trimester of pregnancy.